QTiME-Fostering Dimensional Learning in 21st Century - Ajjampur, Bala; Prasad, Krishna V. (Journal of Engineering Education Transformations, 2015)
Learning in 21st century is learning in knowledge era. The functions of 20th century schools and universities need to change to foster new way of leaming.Atransition must be made to deal with the traits of Gen-Y and perhaps Gen-M (multigeneration) to create new ways of learning. A global reach to educational resources from anywhere and at any time, the functions of schools as information deliverers diminish significantly. To foster nonassessment based learning,there is a need to provoke learning in multiple dimensions. QTiME learning is such an attemptwith QTiME specific leamingquadrantsenabled by simplistic, yet universal and actionable steps. These steps promote cyclical learning to continuously bridge the learning gaps. These QTiME specific dimensions, learning quadrants, the steps and their goals are a paradigm shift in learning to deliver a 21st century learning outcomes.